Effect of lead on strength behaviour for spiked contaminated soil - Mohamad Azwan Zahari,; Muhammad Hafeez Osman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Deterioration of geo-environmental quality caused by the heavy metal in contaminated soil leads to changes in physical, mechanical, and chemical properties of soil. It is important to study the effect of contamination of the geotechnical properties of soil. The main aim of this research is to study the impact of lead and incubation time on polluted soil compressibility. The soil samples were got from Kaolin Malaysia Sdn Bhd in Tapah Perak. The soil samples were spiked with two concentrations of lead nitrate (1000 mg/kg and 2000 mg/kg), and were incubated for 7, 14, 21, and 28 days. The contaminated samples were created using a mixture of distilled water and lead nitrate. The physical, mechanical, and chemical properties of control and contaminated samples were assessed to analyse the effect of lead nitrate on these properties. Lead nitrate causes the increasing of plastic limit and liquid limit, reduction of maximum dry density and optimum moisture content. In addition, the unconfined compressive strength was decreased by 4.2% for 1000mg/kg while 24.3% with 200 mg/kg. This is with increasing concentration of lead nitrate as well as incubation period. Collapsibility increases with increased concentration of lead nitrate and time of incubation due to increased compressibility capacity. The important thing about this study is to provide a database for the future development of the site area contaminated with heavy metals such as landfill, landfill, agriculture and industry.